2019
DOI: 10.3390/vaccines7040149
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cells and PD-1/PD-L1 Blockade Upregulate the Expression of PD-1, CTLA-4, TIM-3 and LAG-3 Immune Checkpoints in CD4+ T Cells

Abstract: : Triple negative breast cancer (TNBC) is the most aggressive breast cancer subtype, and it exhibits resistance to common breast cancer therapies. Immune checkpoint inhibitors (ICIs) targeting programmed cell death 1 (PD-1) and its ligand, PD-L1, have been approved to treat various cancers. However, the therapeutic efficacy of targeting PD-1/PD-L1 axis in breast cancer is under clinical investigation. In addition, the mechanisms of action of drugs targeting PD-1 and PD-L1 have not been fully elucidated. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 53 publications
(65 reference statements)
2
62
0
Order By: Relevance
“…Together, these data suggested that blocking one IC or IC ligand can result in the upregulation of alternative ICs, which potentially leads to T cell exhaustion [56] and gives rise to compensatory mechanisms for tumor cell survival and immune response evasion leading to acquired resistance [20,41]. In parallel with this, we previously investigated the effect of blocking PD-1 and PD-L1 on CD4 + T cells, including Tregs, using a co-culture model of the MDA231 human TNBC cell line [20]. We found that the single or dual blockade of PD-1 and PD-L1 resulted in the upregulation of other ICs on CD4 + T cells, such as TIM-3, CTLA-4 and LAG-3, indicating the emergence of compensatory mechanisms that potentially lead to resistance to ICIs [20].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Together, these data suggested that blocking one IC or IC ligand can result in the upregulation of alternative ICs, which potentially leads to T cell exhaustion [56] and gives rise to compensatory mechanisms for tumor cell survival and immune response evasion leading to acquired resistance [20,41]. In parallel with this, we previously investigated the effect of blocking PD-1 and PD-L1 on CD4 + T cells, including Tregs, using a co-culture model of the MDA231 human TNBC cell line [20]. We found that the single or dual blockade of PD-1 and PD-L1 resulted in the upregulation of other ICs on CD4 + T cells, such as TIM-3, CTLA-4 and LAG-3, indicating the emergence of compensatory mechanisms that potentially lead to resistance to ICIs [20].…”
Section: Discussionmentioning
confidence: 96%
“…In parallel with this, we previously investigated the effect of blocking PD-1 and PD-L1 on CD4 + T cells, including Tregs, using a co-culture model of the MDA231 human TNBC cell line [20]. We found that the single or dual blockade of PD-1 and PD-L1 resulted in the upregulation of other ICs on CD4 + T cells, such as TIM-3, CTLA-4 and LAG-3, indicating the emergence of compensatory mechanisms that potentially lead to resistance to ICIs [20]. Other studies have also shown that resistance-mediated mechanisms in response to PD-1 or PD-L1 blockades are associated with the overexpression of alternative ICs in murine and human studies [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Culturing of cancer cells with immune cells, or onco-immune co-culturing, has been used to study immune interactions between cancer cells and tumor associated macrophages (TAMs) [21][22][23]. Castellaro et al co-cultured MCF-7 breast cancer cells with TAMs and found TAMs promoted cell proliferation and metastasis.…”
Section: Introductionmentioning
confidence: 99%